Methods for capturing African fish eagles on water - Hollamby, Simon; Afema-Azikuru, Josephine; Bowerman, William W.; Cameron, Kenneth N.; Dranzoa, Christine; Gandolf, A. Rae; Hui, Gretchen N.; Kaneene, John B.; Norris, Amanda; Sikarskie, James G.; Fitzgerald, Scott D.; Rumbeiha, Wilson K. (Wildlife Society Bulletin, 2004)
Twelve adult African fish eagles (Haliaeetus vocifer) were captured on water using a floating fish “snare vest” on Lake Victoria near Entebbe and Lake Mburo in Uganda. The snare vest comprised 8–12 monofilament nylon snares attached to a floating 15–25-cm Nile tilapia (Oreochromis niloticus). Capture success was 17% of birds that struck the bait at Lake Mburo and 10% at Lake Victoria. The success rate was dependent on multifactorial local site conditions, operator experience, and snare design. The methods described are the first detailed report on the capture of this species, and the snare vest highlights subtle variations in technique from those reported for the capture of other large eagle species.
Keywords: African fish eagle; Floating fish snare capture methods; Haliaeetus vocifer; Snare vest; Uganda